Assessment of Drug Sensitivity of Different Urinary Isolates to Nitrofurantoin and its Comparison with Other Drugs- A Retrospective Study - Aditi Goyal; Kiranjeet Kaur (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Uncomplicated Urinary Tract Infection (UTI) is one of the most common indications for antibiotic use in the community. However, gram negative organisms that are predominant cause of UTI are becoming increasingly resistant to commonly used antibiotics. Consequently, empiric therapy is likely to fail resulting in increasing number of patients with uncomplicated UTI requiring hospitalisation for intravenous antibiotics as there are no oral treatment options left. Aim: To assess the susceptibility trends of urinary isolates to panel of antibiotics with particular reference to nitrofurantoin. Materials and Methods: The present retrospective study was conducted at Adesh Hospital Bathinda, Punjab, India, for a period of one year from April 2020 to April 2021. Kass criteria was followed for interpretation of significant bacteriuria according to which significant growth is considered if number of colony is more than 105 Colony Forming Unit (CFU)/mL. Culture positive were analysed by gram staining and on the basis of colony characteristics, gram staining, final identification was done using Vitek 2 compact system. Statistical analysis was done using Chi-square test. Results: A total of 392 urinary isolates were identified during the study period. Out of the 392 isolates, 316 (80.6%) were gram negative isolates and 76 (19.4%) were gram positive isolates. Maximum sensitivity was shown to nitrofurantoin, 88% in case of gram negative isolates and 76% in case of gram positive isolates. Conclusion: Nitrofurantoin is an effective therapeutic agent in the treatment of UTI. It has been used for a long time, but the emergence of antibiotic resistance and the decline in newly developed antibiotics has increased interest in the treatment of bacterial UTI with this antibiotic.